Education and support needs in patients with head and neck cancer: A multi‐institutional survey. Issue 11 (12th January 2017) - Jabbour, Joe; Milross, Chris; Sundaresan, Puma; Ebrahimi, Ardalan; Shepherd, Heather L.; Dhillon, Haryana M.; Morgan, Gary; Ashford, Bruce; Abdul‐Razak, Muzib; Wong, Eva; Veness, Michael; Palme, Carsten E.; et al.
Abstract : BACKGROUND: Head and neck cancer (HNC) encompasses a diverse group of tumors, and thus providing appropriate and tailored information to patients before, during, and after treatment is a challenge. The objective of the current study was to characterize the experience and unmet needs of patients with HNC with regard to information and support provision. METHODS: A 28‐question, cross‐sectional survey was completed by patients treated for HNC at 1 of 4 institutions in New South Wales, Australia (Chris O'Brien Lifehouse and Liverpool, Westmead, and Wollongong hospitals). It consisted of the adapted Kessler Psychological Distress Scale and questions assessing information quality, quantity, and format. RESULTS: A total of 597 patients responded. The mean age of the patients was 58 years (range, 21‐94 years) with 284 men and 313 women (1:1.1). The majority of patients reported information concerning the disease process (76%), prognosis (67%), and treatment (77%) was sufficient, and approximately 50% reporting having received little or no information regarding coping with stress and anxiety. A substantial percentage of patients reported receiving minimal information concerning psychosexual health (56%) or the availability of patient support groups (56%). The majority of patients preferred access to multiple modes of information delivery (72%), with the preferred modality being one‐on‐one meetings with a health educator (37%) followed by internet‐based written information (19%). CONCLUSIONS: Patients with HNC are a diverse group, with complex educational and support needs. Patients appear to be given information regarding survivorship topics such as psychological well‐being, patient support groups, and psychosexual health less frequently than information concerning disease and treatment. Verbal communication needs to be reinforced by accessible, well‐constructed, written and multimedia resources appropriate to the patient's educational level. Cancer 2017;123:1949–1957 . © 2017 American Cancer Society . Abstract : Patients with head and neck cancer have complex educational and support needs because of tumor and patient diversity. In the current study, patients highlight unmet informational needs regarding survivorship topics.